Comparison of intraincisional vs intraperitoneal bupivacaine for the control of postoperative pain after laparoscopic cholecystectomy - Bacha, Umar Qadir; Mushtaque, Majid; Tahir, Sifna (International Surgery Journal, 2019)
Background: The aim of this study was to compare the efficacy of infiltration of local anaesthetic bupivacaine at incision site (port site) and intraperitoneally on postoperative pain in patients undergoing laparoscopic cholecystectomy. Methods: This was a randomized controlled study carried out on patients undergoing laparoscopic cholecystectomy. The patients were divided into three groups of 60 patients each. Group 1 was the control group which did not receive either intraincisional or intraperitoneal bupivacaine. Group 2 received intraincisional bupivacaine 0.25% 20 ml, while group 3 received 20 ml solution of bupivacaine 0.25% 20 ml intraperitoneally. Postoperative pain was recorded for 24 hours post-operatively. Results: The incidence of abdominal pain was significantly lower in the group which received intraincisional bupivacaine upto 12 hours postoperatively. Right shoulder pain was low in group receiving intraperitoneal bupivacaine as compared to group 2, but it was not statistically significant. Conclusions: Intraincisional (port site) infiltration of bupivacaine is more effective than intraperitoneal infiltration for postoperative pain relief after laparoscopic cholecystectomy. It is easier to apply and there is less requirement of postoperative analgesics.